Phenolic Compounds of Justicia gendarussa Show Pharmacological Potentials Against Pain, Oxidation, Hyperglycemia, Diarrhea, and Microbes: Phytopharmacological and Computational Approaches. - Munny, Farzana Akter; Islam, Mehedi; Akter, Mahafuza; Ferdousi, Mushtahsin; Asif, Md. Moaz Ahmed; Hossain, Md. Solaiman; Sharmin, Sabrina; Zahidul Islam, Md; Hossain, Md. Aslam; Islam, Md. Rabiul; Banerjee, Baisakhi (BioMed Research International, 2025)
Background: Justicia gendarussa is a branched shrub spread across Indian, Sri Lankan, and Malaysian forests. It has been widely used across many countries to treat asthma, rheumatism, colics in children, eczema, and HIV. The study goal was to investigate the phytoconstituents from J. gendarussa and to discover its therapeutic potential against various disease conditions. Methods: The plant sample was collected, dried, and grinded into coarse powder which was then soaked in methanol for 2 weeks. After the maceration process, the crude methanolic extract was subjected to solvent–solvent partitioning into four different fractions: n‐hexane soluble fraction (HSF), dichloromethane soluble fraction (DMSF), ethyl acetate soluble fraction (EASF), and aqueous fraction (AQF). DMSF was chemically evaluated through chromatographic separation, and all the fractions including the crude methanolic extracts were assessed for their potential pharmacological activities against pain, oxidative stress, hyperglycemia, diarrhea, and microbes following standard protocols. Results: Chemical investigation results in the isolation of lupeol, β‐sitosterol, and 1‐monostearin. The structures of the compounds were elucidated through meticulous NMR spectroscopic analysis. In a DPPH free radical scavenging assay, prominent action was noticed by EASF, with a median inhibition concentration (IC50) of 24.207 g/mL in comparison to the BHT with an IC50 value of 23.159 g/mL. In central analgesic activity, all the results were highly significant, with the highest (233.47%) time elongation in comparison to the control, observed after 90 min at 600 mg/kg b.w. and maximum peripheral analgesic activity of 61.96% was found at a dose of 600 mg/kg b.w. Two test doses (600 and 400 mg/kg b.w.) demonstrated substantial hypoglycemic and antidiarrheal effects that became more pronounced over time. The isolated compounds demonstrated impressive binding scores when interacting with glutathione reductase (3GRS), mu‐opioid receptor (MOR), kappa opioid receptor (KOR), and glucose transporter 3 (GLUT 3) receptors. However, their performance was notably lacking in terms of binding with cyclooxygenase‐2 (COX‐2) and dihydrofolate reductase (DHFR) receptors. Conclusion: Three isolated phytochemicals demonstrate promising binding affinities with the receptor molecules that support the pharmacological findings of this study. However, additional research needs to be conducted to isolate more phytoconstituents and affirm the pharmacological potential of J. gendarussa.